Feedback Effects and Asset Prices - OZDENOREN, EMRE; YUAN, KATHY (Journal of Finance, 2008)
ABSTRACT Feedback effects from asset prices to firm cash flows have been empirically documented. This finding raises a question for asset pricing: How are asset prices determined if price affects fundamental value, which in turn affects price? In this environment, by buying assets that others are buying, investors ensure high future cash flows for the firm and subsequent high returns for themselves. Hence, investors have an incentive to coordinate, which may generate self‐fulfilling beliefs and multiple equilibria. Using insights from global games, we pin down investors' beliefs, analyze equilibrium prices, and show that strong feedback leads to higher excess volatility.